Β‐Meso Covalently linked AzaBODIPY‐Pd(II) Dipyrrin Conjugate. Issue 1 (25th January 2016) - Kumar, Ankit; Kumar, Sunit; Chatterjee, Tamal; Ravikanth, Mangalampalli
Abstract: The first example of azaBODIPY‐metal dipyrrin conjugate such as covalently linked azaBODIPY‐Pd(II) dipyrrin conjugate where the meso ‐carbon of Pd(II) dipyrrin moiety was linked to β‐ pyrrole carbon of azaBODIPY moiety was synthesized over sequence of facile steps under simple reaction conditions. The compound azaBODIPY‐Pd(II) dipyrrin conjugate is freely soluble in common organic solvents and characterized by HR‐MS, 1D & 2D NMR, X‐ray crystallography, absorption, fluorescence and electrochemical techniques. The X‐ray structure revealed that the azaBODIPY and Pd(II) dipyrrin moieties are almost orthogonal to each other with a dihedral angle of 80°. The spectral and electrochemical studies supported weak interaction between azaBODIPY and Pd(II) dipyrrin moieties in conjugate and marginally influences each other's electronic properties. Abstract : Synthesis, structure and properties of the first example of covalently linked azaBODIPY‐Pd(II)dipyrrin conjugate are described. The X‐ray structure revealed that the azaBODIPY and Pd(II) dipyrrin moieties are almost orthogonal to each other with a dihedral angle of 80°. The spectral and electrochemical studies supported weak interaction between azaBODIPY and Pd(II) dipyrrin moieties in conjugate and marginally influences each other's electronic properties.